Historie and Geschchte in Heidegger’s Black Notebooks - Vicenzo Vitiello (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
Beyond the usual necessary remarks on antisemitism in Heidegger´s Black Notebooks, this paper offers a substantial paradox: Black Notebooks (1931-48), the exposition of an unceasing craftwork on the fate of the world (his own?), revolve around two difficult notions to translate, Geschichte and Historie. They are both usually understood, the former as a chronological account of contents that «really» happened in time (history strictly speaking), the latter as the more or less self-interested writing of these (historiography).Heidegger dismisses this interpretation (that would involve «something» separate from its narrative), and offers instead to understand both notions as selfrepresentation. Geschichte would correspond to the way in which, departing from the —interpreted— development of being, this accounts for itself, for its delivery and exhaustion, awaiting a new start. On the contrary, Historie would correspond to the «techno-scientific» representation with which Modernity accounts for itself and its past, as the secularized degradation of Christianity. The paradox then is that, on the one hand, it is Geschichte (as «history-of-being») that would understand Historie as the latest turn of events in some wandering (considering that both movements would have been coincident in Europe in the 1930s), which would lead to its self-destruction. Yet on the other hand, Historie itself accounts for Seinsgeschichte as just another way, among others, (not the most fortunate or scientific) to explain history. Thus, the rootless (devoid of «pagus»: the country) West would head towards decline. Heidegger: a committed pagan, a Christian in spite of himself.